Over-policing Black bodies: the need for multidimensional and transformative reforms - Jones-Brown, Delores (Journal of ethnicity in criminal justice, 2021)
This special issue of JECJ presents empirical evidence, both qualitative and quantitative, that despite several decades of attempted police reform, Blacks continue to experience policing as a repressive social institution, whether they are engaged in crime or not. The research reveals continued patterns of racially disparate treatment during traffic stops, in police response to protestors, and in mainstream media representations of protest events. Consistent with this special issue’s theme, the over-policing of Black bodies is shown to extend beyond mere “perception” to a lived experience that is documented via social media and the narratives of individuals, including former police officers, directly affected by repeat and aggressive police encounters. The researchers make several recommendations to change the current empirical reality. Their reform recommendations include: altering current police training to center the needs of the community as identified by a broad spectrum of residents, especially those who have experienced multiple forms of trauma; the reallocation of police funding to community-based crime prevention efforts; banning officers from requesting consent to search during vehicle stops;encouraging greater participation of highly policed populations in local governance and political processes; and, eliminating racial categories in government-sponsored crime statistic reports. By recognizing existing racialized patterns and working to deliberately uncouple Black racial identity from criminal identity, the U.S. can begin to reverse a long-standing culture of violence within policing that disproportionately targets Blacks.